2019
DOI: 10.1007/s40520-019-01297-1
|View full text |Cite
|
Sign up to set email alerts
|

Disability trajectories and mortality in older adults with different cognitive and physical profiles

Abstract: Background Cognitive and physical deficits independently raise the risk for negative events in older adults. Less is known about whether their co-occurrence constitutes a distinct risk profile. This study quantifies the association between cognitive impairment, no dementia (CIND), slow walking speed (WS) and their combination and disability and mortality. Methods We examined 2546 dementia-free people aged ≥ 60 years, part of the Swedish National study on Aging and Care in Kungsholmen (SNAC-K) up to 12 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…In the present study, we have demonstrated that, although the patients suffered mainly mild strokes with low NIHSS scores, cognitive and motor impairments as well as concurrent impairments are prevalent, as the majority of patients with impaired MoCA scores also had impaired SPPB scores and vice versa. Concurrent motor and cognitive impairments have been shown to predict poor prognosis as, for example, an increased risk of developing dementia in stroke-free populations [43,44], and there is reason to believe that these impairments can impact recovery and everyday life [45]. Therefore, we believe that, as part of the routine follow-up protocol after stroke, assessments of cognition and global motor functions should be performed to gain more information that may be relevant for prognosis and may indicate a need for continued rehabilitation even 3 months after a stroke [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have demonstrated that, although the patients suffered mainly mild strokes with low NIHSS scores, cognitive and motor impairments as well as concurrent impairments are prevalent, as the majority of patients with impaired MoCA scores also had impaired SPPB scores and vice versa. Concurrent motor and cognitive impairments have been shown to predict poor prognosis as, for example, an increased risk of developing dementia in stroke-free populations [43,44], and there is reason to believe that these impairments can impact recovery and everyday life [45]. Therefore, we believe that, as part of the routine follow-up protocol after stroke, assessments of cognition and global motor functions should be performed to gain more information that may be relevant for prognosis and may indicate a need for continued rehabilitation even 3 months after a stroke [45].…”
Section: Discussionmentioning
confidence: 99%
“…We found higher walking speed to attenuate decline in odor identification, an effect that persisted when excluding participants who converted to dementia. Gait speed represents an important marker of general physical condition ( 22 ). As such, gait speed may reflect overall health in a similar manner as the state of the olfactory system ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neurological/psychiatric predictors encompassed current diagnosis of depression (ICD-10 F32) and history of head trauma (ICD-10 S06). Gait speed (m/s) was included as a measure of mobility and general health status ( 22 ) and assessed by asking participants to walk 6 m at their usual speed. Participants who reported difficulties walking, or for whom the assessment had to be carried out in a restricted space, were asked to walk 2.4 m. We further considered polypharmacy, measured as total number of medications ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Concurrent motor and cognitive impairments have been shown to predict poor prognosis as, for example, an increased risk of developing dementia (44,45), and there is reason to believe that these impairments can impact recovery and everyday life (46). Therefore, we believe that, as part of the routine follow-up protocol after stroke, assessments of cognition and global motor functions should be performed to gain more information that may be relevant for prognosis and may indicate a need for continued rehabilitation even three months after a stroke (46).…”
Section: Discussionmentioning
confidence: 99%